2022
DOI: 10.3389/fpubh.2021.788074
|View full text |Cite
|
Sign up to set email alerts
|

Detecting COVID-19-Related Fake News Using Feature Extraction

Abstract: Since its emergence in December 2019, there have been numerous posts and news regarding the COVID-19 pandemic in social media, traditional print, and electronic media. These sources have information from both trusted and non-trusted medical sources. Furthermore, the news from these media are spread rapidly. Spreading a piece of deceptive information may lead to anxiety, unwanted exposure to medical remedies, tricks for digital marketing, and may lead to deadly factors. Therefore, a model for detecting fake new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Thus, the results of our study differed from those of previous studies, which showed that people with low health literacy are more likely to have problems in their lives. Information about the COVID-19 pandemic provided by the media is both trusted and not trusted and has been spread rapidly to keep the public abreast of the global situation and to prevent infection ( Khan et al, 2022 ). In the survey about COVID-19 Information Sources and Mental Health, trusting social media may worsen mental health ( Patwary et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the results of our study differed from those of previous studies, which showed that people with low health literacy are more likely to have problems in their lives. Information about the COVID-19 pandemic provided by the media is both trusted and not trusted and has been spread rapidly to keep the public abreast of the global situation and to prevent infection ( Khan et al, 2022 ). In the survey about COVID-19 Information Sources and Mental Health, trusting social media may worsen mental health ( Patwary et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al [22] discovered that participants' perceptions of false news transferred to an adjacent brand advertising when they saw an adjacent brand commercial. The direct impact of behavioral intentions on brands is employed to investigate the consequences of fake news.…”
Section: State-of-the-arts Fake News Detection Techniquesmentioning
confidence: 99%
“…It is possible that detecting bogus news early on may assist to prevent it from spreading further on social media platforms. There have been several subjective research into the components of false news published in the social psychology literature [22,32,38,39], but there have been relatively few quantitative investigations to validate these psychological factors. Regarding spreading false information on social media, the echo chamber effect has a tremendous impact, as seen above.…”
Section: Fake News Detection Taxonomymentioning
confidence: 99%
See 2 more Smart Citations